Analisis Manajemen Waktu pada Surat Al Ashr dalam Tafsir Al Qur’an Al Adzim Karya Ibnu Katsir - Pindra Rama Ardiansa; Sudarmadi Putra (Jurnal Ilmiah Dan Karya Mahasiswa, 2024)
This research aims to analyze the concept of time management contained in Surah Al Ashr through the interpretation of Al Quran Al Adzim by Ibnu Katsir. The method used in this research is a literature study using a qualitative descriptive approach. Data collection was carried out using documentation study techniques. The research results show that in Surah Al Ashr, Allah swears in the name of time. In Surah Al Ashr, people are said to lose money if they cannot manage their time well. Also mentioned are the groups of people who are not included as people who suffer losses, namely people who believe, do good deeds, give advice in the truth and people who are patient.